Essentials of haematology - Kawthalkar, M. Shirish (Jaypee Brothers Medical, 2006)
Updates each chapter to educate students on the current knowledge and practices in the field of Haematology.The figures and illustrations highlight the important morphological details which facilitates better understanding This volume is a concise textbook of haematology which caters to the needs of undergraduates inmedicine.